The The Effect of Ambon Banana Smoothies on Hemoglobin Levels in Third Trimester Pregnant Women with Anemia at TPMB Wahdiati - Putri, Ade Mona Julia; Carolin, Bunga Tiara; Azzahroh, Putri (Rajaki of Tulip Medika Publisher, 2025)
Background: Anemia is a condition of low oxygen levels in the blood caused by a lack of iron intake, which is necessary for the formation of hemoglobin. There are two ways to prevent anemia: pharmacologically, by taking iron tablets, and non-pharmacologically, by consuming Ambon banana smoothies. Purpose: To determine the effect of administering Ambon banana smoothies on hemoglobin levels in pregnant women in their third trimester with anemia at the Wahdiati Maternity Clinic in Tangerang Regency. Methods: The data analysis used was univariate analysis. The average hemoglobin level before the administration of Ambon banana smoothies in the control group was 10,56 g/dL, while in the intervention group it was 10,29 g/dL. The average hemoglobin level after administration of Ambon banana smoothies in the control group was 11,50 g/dL, while in the intervention group it was 12,36 g/dL. The results of the bivariate analysis using an independent t-test yielded a p-value of 0,001 (p < 0,05). This finding indicates that there was a significant difference in the increase in hemoglobin levels between the control group and the intervention group. Conclusion: Ambon banana smoothies are a safe and effective alternative therapy for increasing hemoglobin levels. Further research with larger samples and longer intervention durations is recommended to reinforce these findings Keywords: anemia in pregnant women, hemoglobin levels, ambon banana smoothies, third trimester, nutritional intervention.